Exploring Self-Directed Learning to Enhance Arabic Language Skills among Pre-Service Teachers at an Indonesian Islamic University - Muhammad Zaenuri; Muhammad Nur Kholis; Fouad Larhzizer; Muhammad Arief; Wafiya Nur Syahida; Nia Nur Faizah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2026)
This study aims to investigate the level of Self-Directed Learning (SDL) skills and the factors influencing them among preservice Arabic teachers in Indonesia. This study used a mixed-method approach with a sequential explanatory design. Quantitative data were collected through questionnaires completed by 262 students of the Arabic Language Education Study Program and supported by Focus Group Discussions. The results showed that students’ SDL levels varied, with learning strategies categorized as high (Mean = 3.71) and learning activities categorized as moderate (Mean = 3.18). Self-efficacy, social support, and institutional facilities were identified as the main supporting factors, while low intrinsic motivation and dependence on external feedback became the major inhibiting factors. The findings indicate that students’ SDL skills have developed but still require improvement, especially in motivation and self-evaluation. Therefore, institutional support through interactive learning strategies and digital learning resources is needed to strengthen students’ learning independence.